2018
DOI: 10.3390/app9010094
|View full text |Cite
|
Sign up to set email alerts
|

Tarantula: Design, Modeling, and Kinematic Identification of a Quadruped Wheeled Robot

Abstract: This paper firstly presents the design and modeling of a quadruped wheeled robot named Tarantula. It has four legs each having four degrees of freedom with a proximal end attached to the trunk and the wheels for locomotion connected at the distal end. The two legs in the front and two at the back are actuated using two motors which are placed inside the trunk for simultaneous abduction or adduction. It is designed to manually reconfigure its topology as per the cross-sections of the drainage system. The bi-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Note that the two subsystems are considered for the ease of kinematic and dynamic formulations with block-2 assumed to be the center block about which the two subsystems are labeled as in Figure 4b. Table 1 lists the Denavit-Hartenberg (DH) parameters notation as adapted in [23] for the two dissections of the hTetro. Table 1.…”
Section: Kinematicsmentioning
confidence: 99%
“…Note that the two subsystems are considered for the ease of kinematic and dynamic formulations with block-2 assumed to be the center block about which the two subsystems are labeled as in Figure 4b. Table 1 lists the Denavit-Hartenberg (DH) parameters notation as adapted in [23] for the two dissections of the hTetro. Table 1.…”
Section: Kinematicsmentioning
confidence: 99%
“…They showed a caterpillar-inspired quadruped robot whichimitatesthe prolegs of caterpillars, and a mudskipper-inspired crawling algorithm based on reinforcement learning, which improves the adaptation of locomotion. Hayat et al [35] designed a quadruped wheeled robot and showed its kinematic formulation. Jia et al [36] tackled the motion stability of quadruped robots with dynamic gait.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%
“…The precedence of the Tarantula-II is based on the first version of the robot here referred as Tarantula-I reported in [27]. The two versions can be compared using the framework for evaluating the autonomy of the self-reconfigurable robot as reported in [28].…”
Section: Introductionmentioning
confidence: 99%